HUBUNGAN NYERI RHEUMATHOID ARTHRITIS DENGAN KEMANDIRIAN DALAM AKTIVITAS SEHARI-HARI PADA MASYARAKAT DIWILAYAH KERJA PUSKESMAS DUMBO RAYA KOTA GORONTALO - Andi Nuraina Sudirman; Abdul Wahab Pakaya (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Degradation ability in daily life activities is a problem that needs to be considered and carried out properly in patients with rheumatoid arthritis. This study aims to determine whether there is a correlation between rheumathoid arthritis pain and independency in daily activities in the community at Dumbo Raya Health Center, Gorontalo City. This type of research is analytic observation with a cross sectional study approach. The samples were taken by using accidental sampling technique with 37 respondents. The chi square test results showedthat(51.4%) of respondents experienced severe pain intensity and (64.9%) of respondents are not independent. The significance value of α = 0.05 which means that there is a correlation between rheumathoid arthtiris pain and independency in daily activities of community at Dumbo Raya Health Center, City of Gorontalo.